Histone Deacetylases (HDACs) and Atherosclerosis: A Mechanistic and Pharmacological Review - Chen, Xiaona; He, Yanhong; Fu, Wenjun; Sahebkar, Amirhossein; Tan, Yuhui; Xu, Suowen; Li, Hong (Frontiers in Cell and Developmental Biology, 2020)
Atherosclerosis (AS), the most common underlying pathology for coronary artery disease, is a chronic inflammatory, proliferative disease in large-and medium-sized arteries. The vascular endothelium is important for maintaining vascular health. Endothelial dysfunction is a critical early event leading to AS, which is a major risk factor for stroke and myocardial infarction. Accumulating evidence has suggested the critical roles of histone deacetylases (HDAC) in regulating vascular cell homeostasis and AS. The purpose of this review is to present an updated view on the roles of HDACs (type I, type II, type IV) and HDAC inhibitors (HDACi) in vascular dysfunction and AS. We also elaborate on the novel therapeutic targets and agents in atherosclerotic cardiovascular diseases.